Integrating Local Culture in the Development of Indonesian Language Teaching Materials for General Education - Kartini' Kartini'; Anita Candra Dewi; M. Nur Hakim; Chece Djafar (AL-ISHLAH: Jurnal Pendidikan, 2025)
Indonesia’s linguistic and cultural diversity presents both opportunities and challenges for language education. While the national curriculum emphasizes uniformity, it often overlooks the sociocultural realities of students across different regions. As a result, Bahasa Indonesia teaching materials rarely incorporate local content, leading to student disengagement and missed opportunities for culturally grounded learning. Despite growing interest in culturally responsive pedagogy, scalable and systematic curriculum development models remain limited. This study addresses that gap by employing the ADDIE instructional design framework in combination with Design-Based Research (DBR) to develop and evaluate culturally integrated Bahasa Indonesia learning materials. The project is implemented in ten schools across five provinces, using Culturally Responsive Pedagogy and Sociocultural Theory as its theoretical foundations. Data collection includes both quantitative assessments and qualitative interviews and observations. The findings indicate substantial learning improvements, including a 40% increase in student engagement, a 25% improvement in reading comprehension, and a 20% rise in writing proficiency. Qualitative data further reveal enhanced teacher-student relationships, increased classroom participation, and stronger cultural identification among students. These outcomes highlight the effectiveness of culturally sensitive materials in supporting both emotional and cognitive student development. The integration of local cultural elements fosters greater connection to learning content and improves overall academic performance. This study provides a scalable, evidence-based model for culturally inclusive curriculum development. Its implications extend to national education policy, teacher training, and subject-area integration, advocating for equity-centered reform in multilingual, multicultural education systems.